FORM OF THE REED WEAVING DANCE PERFORMANCE AT THE NATYARIPTA DRAMA: BENTUK PERTUNJUKAN TARI MENGANYAM BULUH DI SANGGAR NATYARIPTA - Ade Antika Sari; Arbi Julta (SOSIOEDUKASI, 2025)
This study aims to examine the performance form of the Reed Weaving Dance performed at the Natyaripta Studio, Margotentrem Village. The Reed Weaving Dance is a creative dance that depicts the process of weaving reeds into various forms of handicrafts with agile movements and simple yet elegant costumes. This study uses a qualitative method with a case study approach, through data collection techniques in the form of observation, interviews, and documentation. The main interview was conducted with Mrs. Susi Trianasari as a resource person who played an active role in the development of the dance. The results of the study show that the Reed Weaving Dance performance not only displays a series of movements that represent the weaving process, but also contains cultural values such as patience, perseverance, and creativity that are the identity of the Margotentrem community. The accompanying music used is a combination of traditional and modern musical instruments, while the dance properties support the concept of the performance. This research is expected to contribute to the preservation of creative dance arts and increase public awareness of the importance of maintaining and developing local culture.